Three-dimensional characterization and quantitative research of Malan loess microstructure under seismic loading - Wei, Tingting; Wu, Zhijian; Chen, Yanping; Luo, Liang (Frontiers in Earth Science, 2023)
The deformation and failure of loess in high seismic intensity area is closely related to its dynamic vulnerability, which are primarily controlled by the microstructure. A series of dynamic triaxial tests and microstructure tests were performed on intact loess to track and quantitatively characterize the evolution of three-dimensional microstructure during deformation. The microstructural observations were performed using micro-CT on the samples after vibration times and the microstructure parameters (including pore radius, elongation, orientation, coordination number, pore throat area and channel length) were obtained by reconstructed pore network model. Results of the study highlight that the loess seismic subsidence originates from both compositional and microstructural characteristics. The intact loess has a loose structure with a high porosity and a few cementations. Upon cyclic loading, breakdown of cementations and contact led to the failure of loess structure, following by particle rearrangement. With increasing vibration times, the spaced and inter-aggregate pores turn into intra-aggregate pores, the pore throat size tends to decrease while number tends to increase, the connectivity tends to weaken, and the shape tends to be long and flat. Pores larger than 28 μm mainly provide spatial conditions for collapse deformation under seismic load. In addition, under the ultimate loading, cracks of large volume occur inside the sample. This research provides further insights into loess seismic subsidence from the perspective of three-dimensional microstructures and research basis for analysing the stability of loess slopes and foundations by combining finite element and discrete element.